LEVEL OF KNOWLEDGE, INDIVIDUAL CHARACTERISTICS AND ANTIBIOTIC CONSUMPTION BEHAVIOR AT TANAKARAENG VILLAGE, GOWA, INDONESIA - Hapsari, Bramantyas Kusuma; Maharani, Aaliyah Pryanditha; Padad, Andi Tenri (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2023)
Overuse or inappropriate antibiotics can cause resistance so that the genetic ability of bacteria become less or not sensitive to antibiotics through resistance mechanisms acquired, spontaneous mutation, and transferred resistance. However, if society have not changed the way they consume or use antibiotics rational, new antibiotics also will the same with now and be ineffective. Knowing the distribution of knowledge levels, individual characteristics, and behavior consumption antibiotics in society rural. This research is a cross sectional study. Questionnaire used to get information knowledge , characteristics and behavior consumption antibiotics in society Village Tanakaraeng Regency Gowa , South Sulawesi, Indonesia. A total of 124 respondents were involved in study this . There is 74 respondent (59.7%) from group age 20 – 35 years old, majority woman that is 91 respondent (73.4%) with complaint main most sick of  tooth and headache that is 25 respondent (20.2%). Place purchase antibiotics the most is pharmacy with 62 respondent (50%), majority from college is 43 respondent (34.7%). There is 70 respondent (56.5%) with good knowledge. Based on behavior consumption antibiotics there is 110 respondents (88.7%) that have behavior irrational. The people of Tanakaraeng Village already have good knowledge about antibiotics, but majority own behavior irrational in consuming antibiotics